2016
DOI: 10.4103/0975-962x.184650
|View full text |Cite
|
Sign up to set email alerts
|

Bone manipulation procedures in dental implants

Abstract: The use of dental implants for the rehabilitation of missing teeth has broadened the treatment options for patients and clinicians equally. As a result of advances in research in implant design, materials, and techniques, the use of dental implants has increased dramatically in the past two decades and is expected to expand further in the future. Success of dental implants depends largely on the quality and quantity of the available bone in the recipient site. This however may be compromised or unavailable due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 17 publications
0
55
0
1
Order By: Relevance
“…With the up rise of implant therapy and increased esthetic and functional demands from the patient, the reconstruction of resorbed alveolar ridges has become the basic essentiality for implant therapy. Currently, the reconstruction frequently utilizes one or a combination of periodontal plastic surgical procedures in conjunction with autogenous bone grafting, allogenic bone block grafting, ridge split techniques, distraction osteogenesis, or guided bone regeneration for most predictable outcomes (Mittal, Jindal & Garg, ; Zeiter, Ries, Weir, Mishkin & Sanders, ). However, these surgical procedures are considered highly technique sensitive and it is reported that soft tissue dehiscence and exposure of bone grafts to the oral cavity are common complications, especially in vertical ridge augmentation, and leading to partial or complete loss of the graft material in up to 40% of the cases (Bahat & Fontanesi, ).…”
Section: Discussionmentioning
confidence: 99%
“…With the up rise of implant therapy and increased esthetic and functional demands from the patient, the reconstruction of resorbed alveolar ridges has become the basic essentiality for implant therapy. Currently, the reconstruction frequently utilizes one or a combination of periodontal plastic surgical procedures in conjunction with autogenous bone grafting, allogenic bone block grafting, ridge split techniques, distraction osteogenesis, or guided bone regeneration for most predictable outcomes (Mittal, Jindal & Garg, ; Zeiter, Ries, Weir, Mishkin & Sanders, ). However, these surgical procedures are considered highly technique sensitive and it is reported that soft tissue dehiscence and exposure of bone grafts to the oral cavity are common complications, especially in vertical ridge augmentation, and leading to partial or complete loss of the graft material in up to 40% of the cases (Bahat & Fontanesi, ).…”
Section: Discussionmentioning
confidence: 99%
“…A 25% reduction in bone width in the cervical region and a 40% reduction of width in the labial plate of the bone occurs in the first and third years after extraction. 3 Large resorption which is not offset by rapid bone regeneration can change the structure of the maxilla and mandible bones, thereby rendering the use of dentures problematic. 3 Consequently, it is important to perform socket preservation in order to maintain the alveolar bone after tooth extraction and minimize alveolar bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…The primary role of the implant dentistry is to rehabilitate the stomatognathic system by restoring normal function, speech, contour, and esthetics of the oral cavity, without any harmful effect on the health of the patient . Due to advancement in the design of implant, techniques, and materials today, for the rehabilitation of different clinical problems various types of dental implants are available with very predictable success rate . The dental implants are designed in such a way that primary mechanical stability can be achieved, so that a strong interaction between bone and implant can be achieved for successful osseointegration .…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to advancement in the design of implant, techniques, and materials today, for the rehabilitation of different clinical problems various types of dental implants are available with very predictable success rate. 2 The dental implants are designed in such a way that primary mechanical stability can be achieved, so that a strong interaction between bone and implant can be achieved for successful osseointegration. 3,4 In order to get a good primary stability, threads are incorporated into the implants so that surface area of implant can be increased with proper stress distribution and minimizing the unwanted stresses to the bone-implant interface.…”
Section: Introductionmentioning
confidence: 99%